2021
DOI: 10.21203/rs.3.rs-898511/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation of Graft Maturity with Knee Function Scores Post Anterior Cruciate Ligament Reconstruction: A Retrospective Study

Abstract: BACKGROUND: The relationship between the signal/noise quotient value and knee function scores has not been extensively studied. Thus, we aimed to investigate the correlation between graft maturity and knee function after anterior cruciate ligament reconstruction.METHODS: In this retrospective study, we included patients (n=50; 28 male patients; age, 31.0 years) who underwent anterior cruciate ligament reconstruction with autogenous tendons between August 2016 and August 2018. At 6 months and 2 years postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Some studies have found a correlation between the SNQ values of an ACL graft and the IKDC 2000 scores after ACL reconstruction (r = 20.454; P = .003). 4,17 In fact, the relationship between graft SNQ values and functional outcome is controversial because conventional MRI sequences are susceptible to MRI scanning techniques including multichannel coils and parallel imaging, which can influence both the statistical and the spatial distribution of noise. 2,8 To overcome the above shortcomings, we used T2* mapping in this study to evaluate the relationship between graft maturity and RTS after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found a correlation between the SNQ values of an ACL graft and the IKDC 2000 scores after ACL reconstruction (r = 20.454; P = .003). 4,17 In fact, the relationship between graft SNQ values and functional outcome is controversial because conventional MRI sequences are susceptible to MRI scanning techniques including multichannel coils and parallel imaging, which can influence both the statistical and the spatial distribution of noise. 2,8 To overcome the above shortcomings, we used T2* mapping in this study to evaluate the relationship between graft maturity and RTS after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%